Pemanfaatan Google Scholar Dalam Pencarian Informasi - Alya Ratu Balqis; Alyaumi Hasanah Siregar; Ayu Fridalisa; Muhammad Farhan Maulana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In today's technological developments, many academics, including students, are writing digital documents. However, finding the right reference source and determining whether an article contains elements of plagiarism or is still experiencing difficulties. Until now, many academics have found information from unreliable sources, even though if this continues it can have a negative impact on academics. Therefore, technology through Google provides easy access to handle this by making Google Scholar one of the trusted places to find legitimate articles. This research uses descriptive qualitative method. The author hopes that with this writing, students can obtain more comprehensive information and be able to make it easier for examiners to find plagiarism in student final assignments. Keywords: Information Technology, Google scholar, Information search